The moderating effect of social environment on the relationship between entrepreneurial orientation and entrepreneurial intentions of female students at Nigerian universities - Ekpe, Isidore; Mat, Norsiah (Research Papers, Journals, Case studies, 2012)
The objective of this study was to examine the moderating effect of social environment on the relationship between entrepreneurial orientation and entrepreneurial intentions of undergraduate female students of Nigerian Universities. Female students were chosen because they are more susceptible to social pressures.One of the hypotheses was to test whether social environment moderates the effect of entrepreneurial orientation on entrepreneurial intentions. A quantitative research method (survey) was used to solicit responses from 120 final year undergraduate female students of three University Business Schools in the North, East and West regions of Nigeria.This method was used because Universities in Nigeria offer similar courses and the respondents, according to previous studies in other contexts, show a higher propensity to firm formation. Data were analyzed using descriptive statistics and hierarchical regression. The results indicated that entrepreneurial orientation (self-efficacy and education) had significant positive influence on entrepreneurial intention among female business students in Nigeria. It was also found that social environment (friends’ agreement) moderated the relationship between entrepreneurial orientation (education) and entrepreneurial intentions among the students.Again, the study contributed to the scant literature on entrepreneurial intentions among people in developing countries especially Nigeria. Therefore, the government should focus on ways to encourage entrepreneurship awareness among university students in Nigeria to enhance entrepreneurial intentions and self-employment. The study was limited to female students. Future studies could compare the entrepreneurial intentions of male and female students.